PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABLE INTERVENING KARYAWAN CV. F1 ADVERTISING JEMBER - Ira Puspitadewi Samsuryaningrum (Jurnal Ilmiah Akuntansi Indonesia, 2018)
This research aimed to determine the influence of compensation toward the employees performance by job satisfaction as intervening variable to the employees of CV. F1 Jember Advertising. The data in this research is from the companys’ data in 2013 period. Population of the company in this research are 113 employees. Selection of the sample using stratified random sampling technique. After the stratified random sampling technique, consist of 53 sample as a suitable respondence to used. The analysis technique in this research is path analysis and T test which are to get the comprehensive illustration about the relation between variable. Meanwhile the classic assumption test in this research consist of multikolinieritas test, heteroskedastisitas test, and normalitas test. From the analysis in the obtained result that compensation influence significant positive through job satisfaction toward employees performance.Keyword: Compensation, Employees Performance, Job Satisfaction